Khvurshīd-i pinhān : majmūʻahʻī az guftārʻhā dar bārah-ʻi Hazrat Mahdī (Shinākhthā-yi iʻtiqādī ;, 1984)
On the 12th Shiite imam, Muḥammad ibn al-Ḥasan Mahdī, b. 869; eollection of articles by eminent Shiite scholars.